Science fictions : how fraud, bias, negligence, and hype undermine the search for truth - Ritchie, Stuart (Metropolitan Books ; Henry Holt and Company, 2020)
"Science is how we understand the world. Yet critical flaws in peer review, statistical methods, and publication procedures have rendered a shocking number of scientific studies useless-or worse, badly misleading. Drawing on surprising new data from "meta-science" (the science of how science works), Science Fictions documents the errors that have distorted our knowledge on issues as varied as cancer biology, nutrition, genetics, immigration, education, and extraterrestrial life. Stuart Ritchie's own work challenging an infamous psychology experiment helped spark what's now widely known as the "replication crisis," the realization that many supposed scientific truths cannot be relied upon. Now, he reveals the very human biases, mistakes, and deceptions that undermine the scientific endeavor: from contamination in science labs to the secret vaults of failed studies that nobody gets to see; from outright cheating with fake data to the more common but still ruinous temptation to exaggerate mediocre results for a shot at scientific fame. Yet Science Fictions is far from a counsel of despair. Rather, it's a defense of the scientific method against the pressures and perverse incentives that lead scientists to bend the rules. By illustrating the ways that science goes wrong, Ritchie gives us the knowledge we need to spot dubious research, and points the way to reforms that might save science from itself"- Resumé vydavatel
Keywords: vědecké omyly; vědecké podvody; věda -- metodologie; věda -- etické a morální aspekty; vědecký výzkum -- etické a morální aspekty; scientific errors; scientific misconducts; science -- methodology; science -- ethical and moral aspects; scientific research -- ethical and moral aspects; monografie; monographs